Amyloid precursor proteins are constituents of the presynaptic active zone - Laßek, Melanie; Weingarten, Jens; Einsfelder, Ulf; Brendel, Peter; Müller, Ulrike C.; Volknandt, Walter (Journal of neurochemistry, 2013)
The amyloid precursor protein (APP) and its mammalian homologs, APLP1, APLP2, have been allocated to an organellar pool residing in the Golgi apparatus and in endosomal compartments, and in its mature form to a cell surface-localized pool. In the brain, all APPs are restricted to neurons; however, their precise localization at the plasma membrane remained enigmatic. Employing a variety of subcellular fractionation steps, we isolated two synaptic vesicle (SV) pools from rat and mouse brain, a pool consisting of synaptic vesicles only and a pool comprising SV docked to the presynaptic plasma membrane. Immunopurification of these two pools using a monoclonal antibody directed against the 12 membrane span synaptic vesicle protein2 (SV2) demonstrated unambiguously that APP, APLP1 and APLP2 are constituents of the active zone of murine brain but essentially absent from free synaptic vesicles. The specificity of immunodetection was confirmed by analyzing the respective knock-out animals. The fractionation experiments further revealed that APP is accumulated in the fraction containing docked synaptic vesicles. These data present novel insights into the subsynaptic localization of APPs and are a prerequisite for unraveling the physiological role of all mature APP proteins in synaptic physiology. We deciphered the precise subcellular localization of APP at the nerve terminal. We demonstrate that APP and its family members, APLP1 and APLP2, are constituents of the presynaptic active zone, albeit virtually absent in synaptic vesicles (SV). Our findings open new avenues for understanding the physiological role of the mature APP proteins at synaptic contacts, implying a function in the physiology of neurotransmitter release.